Late Miocene to Early Pliocene blueschist from Taiwan and its exhumation via forearc extraction. (17th June 2015) - Sandmann, Sascha; Nagel, Thorsten J.; Froitzheim, Nikolaus; Ustaszewski, Kamil; Münker, Carsten
Abstract Blueschist facies rocks in the Yuli Belt of Taiwan's Central Range record ongoing subduction of the Eurasian plate. We present a prograde Lu–Hf garnet–whole‐rock age of 5.1 ± 1.7 Ma from a retrogressed blueschist in the Yuli Belt. This age is considerably younger than the previously assumed age of 14–8 Ma for high‐pressure metamorphism in the Yuli Belt and represents the youngest Lu–Hf garnet age ever recorded for blueschist facies metamorphism. The age sheds new light on the palaeogeographic origin and exhumation scenario of the Yuli Belt. We propose that the Yuli Belt originated from the ocean–continent boundary of the Chinese passive margin. It was subducted eastward during collision with the Luzon island arc and rapidly exhumed when the forearc lithosphere was removed from above the continental slab by discrete subduction (extraction). This process reduces the pressure above the continental slab and may prompt the ascent of subducted crust into the opening gap. Thus, it can control the exhumation of high‐pressure rocks.